# f * g * h

• Jan 8th 2010, 04:03 PM
l flipboi l
f * g * h
Hello,

Can you please verify that I did the correct operation?
$
f(x) = 2x-1$

$g(x) = x^2$
$h(x) = 1 - x$

$2(1-x)^2 -1$
$2(1-x^2)-1$
$2-2x^2-1$
$-2x^2-1$

Thanks!
• Jan 8th 2010, 04:09 PM
l flipboi l
Quote:

Originally Posted by l flipboi l
Hello,

Can you please verify that I did the correct operation?
$
f(x) = 2x-1$

$g(x) = x^2$
$h(x) = 1 - x$

$2(1-x)^2 -1$
$2(1-x^2)-1$
$2-2x^2-1$
$-2x^2-1$

Thanks!

$2x^2-4x+1$
• Jan 8th 2010, 04:32 PM
Sudharaka
Dear l flipboi l,

I think intead of ${2(1-x^2)-1}\mbox{ it should be }{2(1-2x+x^2)-1}$
• Jan 8th 2010, 04:50 PM
l flipboi l
Quote:

Originally Posted by Sudharaka
Dear l flipboi l,

I think intead of ${2(1-x^2)-1}\mbox{ it should be }{2(1-2x+x^2)-1}$

Sudharaka,

actually, you're right...you just expanded (1-x^2).
• Jan 8th 2010, 05:06 PM
$f(g[h(x)])=2(g[h(x)])-1=2([h(x)]^2)-1$
$=2(1-x)^2-1=2(1-2x+x^2)-1=2x^2-4x+1$
No I did'nt expand $2(1-x^2)-1,\mbox{ I expanded }{2(1-x)^2-1}$